Cultivable anaerobic and aerobic bacterial communities in the fermentation chambers of Holotrichia parallela (coleoptera: scarabaeidae) larvae - Zhang, Zhen-yu (PLoS One, 2018)
As important pests, scarab beetle larvae survive on plant biomass and the microbiota of the fermentation chamber play an important role in the digestion of lignocellulose-rich diets. However, the cultivable microbes, especially the anaerobic cultivable microbes, are still largely unknown. Here, both cultivable anaerobic and aerobic bacterial communities associated with the fermentation chamber of Holotrichia parallela larvae were investigated. In total bacteria cells directly enumerated by the 4’, 6-diamidino-2-phenylindole (DAPI) staining method, the viable plate counts of cultivable bacteria in the fermentation chamber accounted for 0.92% of proportion. These cultivable bacteria were prone to attach to the fermentation chamber wall (88.41%) compared to the chamber contents. Anaerobic bacteria were dominant in the cultivable bacteria attaching to the fermentation chamber wall (70.20%), while the quantities of anaerobes and aerobes were similar in the chamber contents. Polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE), fingerprinting and sequence analysis of isolated colonies revealed that the cultivable bacteria are affiliated with class γ-Proteobacteria, Bacteroidia, Actinobacteria, Clostridia and β-Proteobacteria. γ-Proteobacteria was the major type of anaerobic cultivable bacteria and even the only one type of aerobic cultivable bacteria. Taken together, our results suggest, for the first time, that anaerobic microbiota are dominant in cultivable bacteria in the special anoxia niche of the fermentation chamber from H. parallela larvae. These bacterial isolates could be a treasure trove for screening lignocellulytic microbes which are essential for the plant biomass digestion of this scarab species.